Unintended Pregnancy and Its Adverse Social and Economic Consequences on Health System: A Narrative Review Article - Mansureh Yazdkhasti; Abolghasem Pourreza; Arezoo Pirak; Fatemeh Abdi (Tehran University of Medical Sciences, 2015)
Unintended pregnancy is among the most troubling public health problems and a major reproductive health issue worldwide imposing appreciable socioeconomic burden on individuals and society. Governments generally plan to control growth of births (especially wanted births as well as orphans and illegitimate births) imposing extra burden on public funding of the governments which inevitably affects economic efficiency and leads to economic slowdown, too. The present narrative review focuses on socioeconomic impacts of unintended pregnancy from the health system perspective. Follow of Computerized searches of Academic, 53 scientific journals were found in various databases including PubMed, EMBASE, ISI, Iranian databases, IPPE, UNFPA (1985-2013). Original articles, review articles, published books about the purpose of the paper were used. During this search, 20 studies were found which met the inclusion criteria. Unintended pregnancy is one of the most critical challenges facing the public health system that imposes substantial financial and social costs on society. On the other hand, affecting fertility indicators, it causes reduced quality of life and workforce efficiency. Therefore lowering the incidence of intended pregnancies correlates with elevating economic growth, socio-economic development and promoting public health. Regarding recent policy changes in Iran on family planning programs and adopting a new approach in increasing population may place the country at a higher risk of increasing the rate of unintended pregnancy. Hence, all governmental plans and initiatives of public policy must be regulated intelligently and logically aiming to make saving in public spending and reduce healthcare cost inflation.